2007
DOI: 10.1021/ie061270e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of CO2 Absorption in Aqueous Sodium Glycinate Solutions

Abstract: The physical solubility and diffusivity of N 2 O and CO 2 in aqueous sodium glycinate (SG) solutions of various concentrations (1.0-3.5 kmol/m 3 ) and temperatures (303.15-323.15 K) were reported. The kinetics of the reaction between CO 2 and SG has been studied using absorption data measured by a wetted-wall column apparatus at various temperatures and concentrations. The second-order rate constant of CO 2 with SG was determined to be k 2 (m 3 kmol -1 s -1 ) ) 1.95 × 10 13 exp(-7670/T), where T is the absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 41 publications
1
57
2
Order By: Relevance
“…However, the influence of these reactions under the conditions employed in the present work could be considered negligible. 2 As regards the carbonic acid formation and reaction, it is very slow and it must be considered of no influence on the system studied. 10 The other parallel reaction abovementioned between carbon dioxide and hydroxyl ions could be negligible due to the low hydroxyl ions concentration in the system, such as different studies have proved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the influence of these reactions under the conditions employed in the present work could be considered negligible. 2 As regards the carbonic acid formation and reaction, it is very slow and it must be considered of no influence on the system studied. 10 The other parallel reaction abovementioned between carbon dioxide and hydroxyl ions could be negligible due to the low hydroxyl ions concentration in the system, such as different studies have proved.…”
Section: Resultsmentioning
confidence: 99%
“…These amines have shown fast regimes of absorption accompanied by a chemical reaction, which has a high importance as regards the aim of capturing higher quantities of carbon dioxide, as well as the scale-up of operation units. The most recent research studies are also related to the development and testing of new reagents and/or amines to capture carbon dioxide, 2 as well as the use of blends of different amines 3,4 with the aim of achieving a certain enhancement in pollutant gas capture, due to their combined action. For these reasons, it is important to determine kinetic data for these kinds of reactions with the aim of understanding the behaviour of different amines or blends when reacting with the carbon dioxide present in a gas stream, so that we can calculate the capture efficiency or the geometrical characteristics 5 to design gas-liquid contactors.…”
Section: Introductionmentioning
confidence: 99%
“…Holst et al (2006) compared the apparent absorption rate constants of CO 2 with different amino acid salt solutions and concluded that they were comparable with alkanolamines. Recently Lee et al studied the physical properties and the absorption kinetics of sodium glycinate as an absorbent of carbon dioxide (Lee et al, 2005(Lee et al, , 2007Song et al, 2006). However, the data available in literature are still too limited to permit a suitable design and optimization of processes using amino acid absorbents.…”
Section: Introductionmentioning
confidence: 99%
“…The increased corrosion rates in the potassium taurate solutions at 353.15 K can be explained by a correlation between the equilibrium constant (K) and temperature [23]. To maintain equilibrium, more iron is dissolved into the solution, which subsequently generates more electrons for the oxidization reduction [24], thereby accelerating the corrosion process [21] so that the main metal corrosion occurs at high temperatures. …”
Section: Effect Of Temperaturementioning
confidence: 99%